Azeotropic distillation, ethanol washing, and freeze drying on coprecipitated gels for production of high surface area 3Y–TZP and 8YSZ powders: A comparative study. Issue 10 (December 2015) - Piva, R.H.; Piva, D.H.; Pierri, J.J.; Montedo, O.R.K.; Morelli, M.R.
Abstract: Coprecipitation is a well-established method for synthesizing yttria-stabilized zirconia (YSZ); however, the hard agglomerates formed during the drying stage make it difficult to obtain high surface area powders. This paper compares azeotropic distillation, ethanol washing, and freeze drying, the most common dehydration methods, and assesses their ability to yield non-agglomerated powders of coprecipitated 3 mol% Y2 O3 (3Y–TZP) and 8 mol% Y2 O3 -stabilized zirconia (8YSZ). Azeotropic distillation most effectively increased the surface area of the powders, yielding 3Y–TZP and 8YSZ powders with specific surface areas of 94.73 and 109.37 m 2 g −1, respectively, and crystallite sizes between 9 and 10 nm. Ethanol washing did not homogenously dry out the precipitate, whereas the freeze drying method promoted the formation of hard agglomerates, as evidenced by the peculiar powder characteristics derived from this technique. Interestingly, the surface area seems to be increased in methods that reduce the crystallization enthalpy on the hydrous zirconia precipitates.